From zero to hero: ramp-up management as a new cross-cutting business process management capability - Tobias Albrecht; Benedict Lösser; Maximilian Röglinger (Information Systems and e-Business Management, 2024)
Abstract Changing business environments challenge and motivate organizations to transform. To remain competitive, organizations need to embrace these dynamics and make radical changes to how work is performed. Business process management (BPM) as a holistic management discipline offers mature methods and end-to-end management activities. However, it is subject to the tension between stability and change. While change through the improvement of existing business processes is well understood, the implementation and scaling of novel business processes have been neglected in BPM research. Hence, this paper proposes business process ramp-up management (BPRUM) as a new cross-cutting capability area for contemporary and future BPM and explores relevant sub-capabilities. Our work synthesizes insights from an exploratory interview study with 21 subject matter experts to advance the understanding of BPM as a corporate capability regarding the implementation and scaling of novel processes. As a result, this study illustrates how BPRUM adds to modern BPM and presents 40 action-oriented sub-capabilities that provide hands-on knowledge and practical guidance for effective BPRUM. Thereby, it serves as a foundation for further theorizing on process ramp-up and for structuring discussions among BPM practitioners.
Keywords: 330; Business process management; Capability development; Interview study; Organizational change; Process ramp-up